Kinda like brothers (Lit. Circle) - Booth, Coe. (New York : Scholastic Inc., 2014)
When his mother takes in a twelve-year-old foster boy, Jarrett is forced to share his room and his friends with the new boy.
School Library Journal, September 2014.
Booklist, September 2014.
New York Times, October 2014.
Horn Book, April 2015.
Bulletin (Center for Children's books), October 2014.
Kirkus Review, July 2014.
Keywords: Foster home care -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; African Americans -- Juvenile fiction; African Americans -- Fiction; Foster home care -- Fiction; Interpersonal relations -- Fiction; Mothers and sons -- Fiction; Realistic fiction; Book sets; Literature circles